Avaliação de aditivos químicos alternativos para aplicação em cimentações de poços de petróleo HPHT - Dantas, Tancredo (2016)
The civil construction industry employs a wide diversity of admixtures developed to use in concrete and mortars, but that exhibits excellent performance for oilwell slurries. Some properties meet analogous functions, for example, antifoam, dispersants or friction reducers, fluid loss control agent and set retarders. This study was developed with the objective to evaluate and specify alternative chemical products to be used as admixtures for the formulation of cement slurries for application in onshore oil wells, characterized by temperatures of 180°F (82°C), mature wells and wells subjected to steam injection. During the study, chemical products were selected according its functions. These additives were specified according to PETROBRAS internal standards and the tests were realized according to API RP 10B standards. Some additives presented great potential for application in cement slurries for high temperatures, including antifoams, fluid loss control agents, dispersants and setting retarders.